Cigarette smoking is associated with difficulties in the use of reappraisal for emotion regulation. (1st May 2022) - Faulkner, Paul; Machon, Sandra; Brown, Chris; Sandrini, Marco; Kamboj, Sunjeev; Allen, Paul
Abstract: Background: Negative emotions can promote smoking relapse during a quit attempt. The use of cognitive reappraisal to self-regulate these emotions may therefore aid smoking cessation. Determining whether smokers exhibit difficulties in the use of reappraisal, and which factors are associated with such difficulties, may aid smoking cessations. Methods: 50 smokers and 50 non-smokers completed an online reappraisal task in which they either reappraised or naturally experienced emotions induced by negatively- and neutrally-valenced images that presented situations in either the 1st-person or 3rd-person perspective. Participants also completed the Difficulties in Emotion Regulation Scale (DERS). Results: Compared to non-smokers, smokers were less successful in using reappraisal to self-regulate emotions elicited by negatively-valenced images (but not neutrally-valenced images). Importantly, this effect was only true for images that were presented in the 1st-person (but not 3rd-person) perspective. Contrary to predictions, there were no group differences in DERS scores. Conclusions: This study provides the first evidence that smokers experience difficulties in the use of reappraisal, particularly in situations that appear to be happening to themselves. Because the use of this regulation technique may help smokers to quit, improving smokers' abilities to use reappraisal, particularly during negatively-valenced situations that directly influence the smoker, may aid smoking cessation. Highlights: During a quit attempt, smokers experience negative emotions that hinder cessation. The use of cognitive reappraisal to self-regulate these emotions may aid cessation. Smokers exhibit deficits in using reappraisal to self-regulate negative emotions.